Ex vitro hardening of sugarcane (Saccharum Species Hybrid) clones for rapid multiplication - TAKU, MENIARI; NAGARAJA, T E; LOHITHASWA, H C; SHIVAKUMAR, K V; YADAV, SURESH (The Indian Journal of Agricultural Sciences, 2021)
The hardening of in vitro raised plantlets is essential for better survival and successful establishment. In the present study an attempt was made to find out the best ex vitro condition (single shade net and double shade net) for hardening of five different clones of sugarcane. The effect of temperature, light intensity and humidity on hardening of elite sugarcane genotypes were evaluated under two different hardening conditions. The results obtained in the present investigation concluded that both the ex vitro acclimatization conditions showed almost similar effect on number of leaves per plant. However, for chlorophyll content (mg/g), root characters, viz. number of roots, root length (cm), root volume (cm3) and survival ability, double shade net was found to be optimum for all the genotypes, viz. CoVC 09-61-02, CoVC 07-06-05, CoVC 09-61-07, CoC 671 and CoVC 10-38-07. Whereas, CoVC 07-06-05 and CoC 671 produced optimum shoot length under single shade net. Hence, it is clear that the double shade net served as better hardening condition as revealed from better survival and development of appropriate morphological characters of all the sugarcane clones.